Refinement of Nasal Reconstruction with a V/Y-alar-perforator Flap. Issue 1 (January 2017) - Feinendegen, Dominik L.; Langer, Martin F.; Roldán, J. Camilo
Abstract : Background: The ala of the nose is vascularized by a dense net of perforators originating from the lateral nasal artery or the angular artery. These vessels reach the ala in a cascade fashion from the alar groove/lateral nasal wall. Based on these vessels, a V/Y flap can be dissected with a wide range of mobility. Materials and Methods: Nineteen patients underwent reconstruction of the nose by means of a V/Y-alar-perforator flap alone or in combination with a myocutaneous rotation flap from the lateral nasal wall and/or from the nasal dorsum for reconstruction of defects at the nasal tip, ala of the nose, and/or lateral nasal wall. All patients were followed up 8 months after surgery in average. Results: There was no prolonged congestion or any tissue loss. All patients presented postoperatively with excellent aesthetic results, and no nasal distortion was observed. Conclusion: The V/Y-alar-perforator flap alone or in combination with a myocutaneous rotation flap proved to be a reliable tool in the armamentarium for reconstruction of nasal tip and alar defects providing good aesthetic results.